Legal status of public scientific organizations as subjects of scientific activity in Ukraine - Verba, Snizhanna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is the result of a study of the issues of legal status, normative and legal regulation, and peculiarities of the functioning of public scientific organizations in Ukraine as subjects of scientific activity. It has been established that public scientific organizations are defined as full-fledged subjects of scientific activity. The legislation provides a list of their types. A developed network of public scientific organizations based on the areas of research and the interests of scientists makes it possible to balance the monopoly of state structures, attract foreign funds, work on obtaining new and implementation of current scientific programs, projects, grants, preparing complex scientific works of scientific teams and individual scientists, implementing the results of scientific research , to present them to specialists and eventually to the general public. However, at the legislative level, it is necessary to additionally prescribe the characteristics and capabilities of each of the main types of public scientific organizations, which have their own differences, to increase their role in interaction with state authorities, institutions and organizations in order to strengthen the influence on socio-economic processes, trends of socio-cultural development society and the state. The main lever for the growth of the influence of these creative associations should be the development of financial support for the encouragement of their creation and activity, the formation of appropriate conditions for the introduction of scientific innovations into industrial practice.